Linear response of field‐aligned currents to the interplanetary electric field. Issue 8 (24th August 2017) - Weimer, D. R.; Edwards, T. R.; Olsen, Nils
Abstract: Many studies that have shown that the ionospheric, polar cap electric potentials (PCEPs) exhibit a "saturation" behavior in response to the level of the driving by the solar wind. As the magnitudes of the interplanetary magnetic field (IMF) and electric field (IEF) increase, the PCEP response is linear at low driving levels, followed with a rollover to a more constant level. While there are several different theoretical explanations for this behavior, so far, no direct observational evidence has existed to confirm any particular model. In most models of this saturation, the interaction of the field‐aligned currents (FACs) with the solar wind/magnetosphere/ionosphere system has a role. As the FACs are more difficult to measure, their behavior in response to the level of the IEF has not been investigated as thoroughly. In order to resolve the question of whether or not the FAC also exhibit saturation, we have processed the magnetic field measurements from the Ørsted, CHAMP, and Swarm missions, spanning more than a decade. As the amount of current in each region needs to be known, a new technique is used to separate and sum the current by region, widely known as R0, R1, and R2. These totals are found separately for the dawnside and duskside. Results indicate that the total FAC has a response to the IEF that is highly linear, continuing to increase well beyond the level at which the electric potentials saturate. The currents within each region have similar behavior. Plain Language Summary: In the ionosphere at high latitudes there are electric fields that are involved with the currents that form the aurora. It is known that the voltage and auroral currents respond to the electric field in the solar wind, which is the product of the solar wind's velocity and an embedded magnetic field. In the past it has been found that as the solar wind's electric field increases, the voltage steadily increases linearly, at first, then levels off. This response is known as electric potential saturation. A number of different theories have been proposed to explain these phenomena. To help solve the puzzle of why the potentials saturate, it is necessary to know more about how the currents respond as well, but measurements of the currents are more difficult than the electric fields. This paper reports results of a study that determined how the currents change as the driving in the solar wind increases, using measurements of magnetic fields taken on five different satellites over several years. It was found that unlike the electric potentials, the currents do not saturate. This result was not expected. Key Points: Field‐aligned currents have a linear response to the interplanetary electric field No saturation is observed for currents within any region or the total transpolar current The combined solar wind and interplanetary magnetic field act as a current source